The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3340/jkns.2017.0505.010
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Delayed Vertebral Collapse : Kummell’s Disease

Abstract: Posttraumatic delayed vertebral collapse, known as Kummell’s disease, is increasing in number of patients. This disease is already progressive kyphosis due to vertebral collapse at the time of diagnosis and it causes intractable pain or neurologic deficit due to intravertebral instability. Treatment is very difficult after progression of the disease, and the range of treatment, in hospital day, and cost of treatment are both increased. Clinical features, pathogenesis and radiologic findings of these disease gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 37 publications
3
74
0
2
Order By: Relevance
“…MRI suggests limited fluid filling in the vertebral body. So Kümmell's disease is also referred to as delayed post-traumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,17]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,18], which is similar to the segmental distribution of the two groups of patients in this study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…MRI suggests limited fluid filling in the vertebral body. So Kümmell's disease is also referred to as delayed post-traumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,17]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,18], which is similar to the segmental distribution of the two groups of patients in this study.…”
Section: Discussionsupporting
confidence: 73%
“…Kümmell's disease is a special type of osteoporotic vertebral compression fracture (OVCF), which is relatively rare in clinical practice [1]. Kümmell's disease is also known as nonunion after OVCF, delayed vertebral osteonecrosis after trauma, and delayed vertebral collapse [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed posttraumatic spinal vertebral body collapse, namely Kummell disease, rst described by Dr. Hermann Kummell in 1985 is a rare and poorly documented disease [1,2]. By de nition, it is a spinal disorder characterized by patients suffered a minor spinal trauma but resulted in a symptomatic, progressive, angular kyphosis after a symptom-free period of time ranging from months to years [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Herrnann Kümmell found in 1891 that patients had no symptoms for weeks to months after minor spinal trauma, but gradually developed into symptomatic, progressive kyphosis [1]. Chronic low back pain was not alleviated and progressively increased.…”
Section: Introductionmentioning
confidence: 99%
“…The most literatures reported that Kümmell's disease is associated with ischemic osteonecrosis and pseudoarthrosis formation [1,9,10]. There are obvious fissures and cavities in Kümmell's disease [11].…”
Section: Introductionmentioning
confidence: 99%